PENGARUH PENDIDIKAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN REMAJA TENTANG BAHAYA MEROKOK DI RT. 13 KELURAHAN ARIO KEMUNING - Dea Mega Arini; Dewi Rury Arindari; Sri Mulia Sari; Shinta Maharani; Lela Aini; Latifah (Jurnal Kesehatan : Jurnal Ilmiah Multi Sciences, 2025)
In Indonesia, the number of deaths due to diseases caused by smoking habits reaches 300 thousand per year. Almost 60 percent of deaths in Indonesia are caused by non-communicable diseases (NCDs) caused by smoking such as stroke, hypertension and heart disease, which are now increasing in number. Adolescence is a transition period from childhood to adulthood with various very critical developments. During this period, there will be very rapid physical, psychological, intellectual growth and high curiosity. During this period, adolescents tend to act and do things without considering them first, this of course often leads adolescents to risky behavior ranging from smoking behavior to promiscuity, drugs and so on. Middle adolescents are adolescents aged 15-19 years (Riskesdas, 2018). The government has made various efforts to overcome the incidence of smoking. One of these efforts is Health education is very necessary to upload awareness, provide or increase public knowledge about maintaining and improving health for themselves, their families and the community, the process of health education in achieving goals through changes in adolescent behavior which is influenced by several factors including the material or message delivered, educational aids or demonstration tools used, the methods used and officers or educators who carry out health promotion. The purpose of the researcher is to determine the effect of health education on the level of knowledge of adolescents in RT.13, Ario Kemuning Village, Palembang. This type of research is Quasi-experimental design (pretest - posttest with control group design). Respondents in this study were 68 male adolescents who smoke. Data collection tools using questionnaires. The normality test using Shapiro - Wilk and statistical analysis using the Wilcoxon test showed an effect on respondents' knowledge before and after being given health education with P-value = 0.000 <0.05 which means, H1 is accepted, meaning there is a significant effect on the provision of health education on adolescent knowledge about the dangers of smoking.